A Novel Mycobacterium cosmeticum-Like Bacterium Isolated from the Ear Swab of a Patient with Otitis Externa - Jeanette W. P. Teo; Janet W. S. Cheng; Roland Jureen; Raymond T. P. Lin (Case Reports in Infectious Diseases)
We describe the identification and characterization of a novel nontuberculous mycobacterium (NTM), isolated from an ear swab of an adult male patient with chronic otitis externa. Genetically, the bacterium is most closely related to Mycobacterium cosmeticum; however, growth and biochemical features indicate that it is distinctly different. Here, we highlight for the first time an unusual NTM that is a probable cause of ear infection.